Factors predicting unfavorable results in tuberculosis treatment: an integrative literature review ( 2001-2005) - Tereza CS Villa; Maria EF Brunello; Ricardo A Arcêncio; Cinthia M Sassaki; Elisângela G Assis; Roxana I Cardozo-Gonzales (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This integrative literature review aimed to survey Brazilian and international publications related to factors predicting unfavorable results in tuberculosis treatment. Consulting LILACS, MEDLINE, PORTAL CAPES, operational and epidemiological articles published between 2001 and 2005 were surveyed. The articles were categorized according to: year, journal, place, type, nature, treatment results and predictive factors. In LILACS, 07 articles were found, 03 of which mentioned only treatment abandonment. The predictive factors were: extreme poverty, non adherence and male gender. In MEDLINE, 14 articles were surveyed, 04 of which mentioned only multidrug resistance. The predictive factors were: alcoholism, non supervision and male gender. In Brazilian publications, the greatest concern referred to the non continuity of treatment. These indicated the lack of supervision as an aggravating factor. In international publications, multidrug resistance was appointed as the main problem. Clinical, social and operational factors strongly contributed to the unfavorable result.